0D/2D mixed-dimensional perovskite constructed by thiol- and disulfide-containing ligands. (27th August 2022) - Yao, Guoying; Zhao, Liang; Zeng, Tao; Yang, Zhenyu
Abstract: Reduced-dimensional (RD) perovskites have shown attractive chemical and physical properties for optoelectronic applications. Incorporating large organic ligands enables infinite tunability in the components and structures. Theoretically, it is feasible to apply multiple types of organic ligands in a single RD crystal to achieve multiple-dimensional perovskites. However, the coexistence of different organic ligands commonly introduces competing crystal growths that inhibit the formation of a more complex crystal structure. Herein, we report a case of mixed-dimensional (MD) perovskite single crystal containing two types of sulfide-containing ligands. We show that the application of ketones can partially oxidize organothiol ligands in the precursor solution. The resultant disulfide-based ligands can be co-incorporated with the thiol-based ligand in a single MD perovskite crystal. X-ray diffraction confirmed that the structure contains both layered and isolated inorganic components constructed by face-sharing lead halide octahedra. Unlike conventional RD structures, the MD perovskite shows an enlarged bandgap with valence band maximum and conduction band minimum being spatially separated, and isotropic optical features, as revealed by x-ray diffraction, spectroscopies, and density functional theory computation.